A STUDY OF CONCEPTUAL METAPHORS IN THE NOVEL “THE GREAT GATSBY” BY F SCOTT. FITZGERALD - Lê Thị Hương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
From the perspective of cognitive linguistics, conceptual metaphor is a form of conceptualization – a cognitive process whose purpose is to convey and shape new ideas. Conceptual metaphor is based on physical interactions as a cognitive mechanism that replaces the logic of abstract concepts with more concrete concepts. Cognitive Linguistics, a branch of linguistics, combine knowledge and research from psychology, neuropsychology and linguistics (Peter, 2008). The study brought the features of a language which is popular in the world, English in this quite new theory. The results for finding out the mappings help English major students understand cognition in general, a brand-new way to our mind. From the perspective of CL, the semantic features of a language are expressed clearly and seem to be more exact. In fact, as Östen (2001) stated that the cognitive approach to identifying sub-context by observing what comes before and after each linguistic construct provides a grounding of meaning in terms of sensorimotor embodied experience. The English language makes extensive use of metaphorical words and phrases. Within the scope of this report, we focus our attention on the conceptual metaphors in “The Great Gatsby” by F. Scott Fitzgerald. Using the view of CL helped us to conduct the research and imply what are expressed in the meaning of 10 expressions in this novel to set up 5 mappings as “AWARENESS IS BODY PART”, “EMOTION IS HEALTH”, “EMOTION IS VIOLENCE”, “LONELINESS IS DARKNESS” and “HAPPINESS IS HANGING IN AIR. Through the above illustrations, we can see the universal, variety and richness in the use of expressions of conceptual metaphors. This research helps students to better understand the meaning and language of the novel. Besides, it can also help English major students in learning language, understand the features of a language better, especially in learning translation and interpretation